Babad tanah Jawi : Mulai dari Nabi Adam sampai tahun 1647 Mulai dari Nabi Adam sampai tahun 1647 / W.L. Olthof ; alih bahasa, H.R. Sumarsono ; penyunting, Floriberta Aning, A. Yogaswara - OLTHOF, W.I.; Sumarsono, HR; Floriberta Aning; Yogaswara, A. (Narasi, 2013)
xii, 800 hlm. 18 cm. (3 eks.)